APLIKASI ZAT PENGATUR TUMBUH DENGAN PUPUK KANDANG DAPAT MENINGKATKAN PRODUKSI BUAH MENTIMUN (Cucumis sativus L.) - PANDE GEDE GUNAMANTA; KETUT TURAINI INDRA WINTEN; ANAK AGUNG GEDE PUTRA (Universitas Mahasaraswati Mataram, 2019)
Research on the application of growth regulators (ZPT) with the type of manure on cucumber fruit production (Cucumis sativus L.), carried out in the experimental garden of the Faculty of Agriculture, Tabanan University, Kediri Tabanan Bali, from February 2018 to April 2018. Using a Randomized Group Design (RACK). The treatment tried consisted of two factors, namely the type of manure and the type of growth agent. The dosing factor of the growth regulator consists of 3 types, namely: Ga = ZPT Atonik dose 0.5 ml l-1 water; Gg = ZPT Gibgro dose 100 mg 10 l-1 water; Gd = ZPT Dekamon dose 0.5 ml l-1 water. Type of manure consists of 3 types, namely: K0 = without manure; Ks = cow manure 4.8 kg polybag-1; Ka = chicken manure 4.8 kg polybag-1, each treatment was repeated three times. The results show that, the interaction between the type of plant growth regulator and the type of manure had a significant effect on the variable total weight of plant fresh fruit-1, and the weight of fresh fruit-1 fruit. The highest total weight of plant-1 fruit was shown by the combination treatment of Atonik ZPT with chicken manure (KaGa) which is 546.67 g or increased by 50.46% compared to the combination of KaGg treatment which is equal to 363.33 g. The treatment of the type of growth regulating agent has a very significant effect on the variable number of fruit plants-1, plant fruit length-1 and weight of fruit-1 fresh fruit. The treatment of ZPT Atonik gives the highest fruit-1 fresh fruit weight which is equal to 349.63 g of fruit or increased by 23.53% compared to the treatment of ZPT Gibgro which gives the lowest value of 263.81 g. The treatment of the single effect of manure has a significant effect on all observed results variables.